Hydrogen-containing silane, surface-modified magnesium hydroxide and halogen-free flame-retardant silicone rubber composition as well as preparation method and application thereof
By surface modification of magnesium hydroxide and combining other materials, halogen-free flame-retardant silicone rubber compositions with higher flame retardant, mechanical and adhesive properties are prepared, which solves the problem of existing silicone rubber materials prone to smoldering at high temperatures and high voltages, and is suitable for electrical and electric vehicles.
Patent Information
- Application Number
- CN202510379946.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-28
AI Technical Summary
The existing halogen-free flame-retardant silicone rubber materials are prone to smoldering at high temperatures and high voltages, and have low flame retardant efficiency and insufficient mechanical properties and bonding properties, which limits their application in the electrical and electric vehicles fields.
By surface modification of magnesium hydroxide using a hydrogen-containing silane and an epoxy-containing silane coupling agent, combined with vinyl silicone oil, a crosslinking agent, a tackifier, a structural control agent and a catalyst, a halogen-free flame-retardant silicone rubber composition with higher flame retardant properties, mechanical properties and bonding properties was prepared.
It achieves higher flame retardant properties, mechanical properties and bonding properties of silicone rubber, adapts to higher temperatures and voltages, and is suitable for electrical and electric vehicles.
Smart Images

Figure CN119874761A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicone rubber, and specifically to a hydrogen-containing silane, surface-modified magnesium hydroxide and a halogen-free flame-retardant silicone rubber composition, and a preparation method and application thereof. Background Art
[0002] Since the domestic and foreign markets have put forward the demand for halogen-free flame retardancy in the wire and cable, transportation, electronic appliances and construction industries, the research and development of "halogen-free flame retardancy" of polymer materials has developed rapidly. The current main halogen-free flame retardants are hydroxide flame retardants, including aluminum hydroxide, magnesium hydroxide, etc. These flame retardants are widely available and inexpensive, but they have low flame retardant efficiency, large addition amounts, and poor compatibility with polymers, which not only increases the cost of raw materials, but also damages the physical and processing properties of the polymer substrate, resulting in a significant reduction in its mechanical properties. Effective solutions to the above problems include: ultra-fine processing of flame retardants, microencapsulation processing, surface treatment, synergistic composite, etc.
[0003] The main chain of silicone rubber is Si-O bond, which has high thermal stability, low flammability, low heat release rate and low flame spread rate. Due to its special flame retardant and high and low temperature resistance, silicone rubber is widely used in the fields of electronics, aerospace and automobile industry as a new type of adhesive material. However, the side groups of the molecular chain of ordinary silicone rubber materials contain carbon-containing groups such as methyl and vinyl, which still have the disadvantage of being flammable and are particularly prone to smoldering. There are great safety hazards. Under excessively high temperatures and excessively strong voltages, silicone rubber may change from smoldering to flaming combustion, thereby limiting its application in the fields of electrical and electric vehicles. Therefore, in order to make silicone rubber adapt to higher temperatures and voltages and improve its flame retardant properties, it is necessary to find a method to effectively improve the flame retardant properties of silicone rubber, while at the same time, its mechanical properties are not significantly reduced after curing, and it has a good bonding effect on the substrate when used as an adhesive.
[0004] Ma Shugang et al. (Study on surface modification of magnesium hydroxide and its flame retardant properties in silicone rubber, Ma Shugang, Wan Zi'an, Liu Xingchi, Wang Shirong, Li Xianggao, Hou Jingwei, Modern Chemical Industry, 2024-4, 146-151) used industrial-grade magnesium hydroxide (MH) as raw material, vinyl triethoxysilane, 3-(aminopropyl) triethoxysilane and ethyl triethoxysilane as modifiers, and prepared modified magnesium hydroxide by wet process. The modified magnesium hydroxide was blended into silicone rubber. It was found that the magnesium hydroxide particles modified with vinyl triethoxysilane and silicone rubber can be better blended and fused, and the vulcanized network structure of silicone rubber after blending is more solid, thereby improving the mechanical properties of the composite material. However, the cohesive density and tensile strength of the silicone rubber composite material prepared by it need to be further improved to meet the requirements of adhesives, especially structural adhesives used to replace traditional mechanical fasteners, for the mechanical properties of silicone rubber. Summary of the invention
[0005] The purpose of the present invention is to overcome the above shortcomings and to provide a hydrogen-containing silane and a preparation method thereof, a surface-modified magnesium hydroxide and a halogen-free flame-retardant silicone rubber composition and a preparation method and application thereof. By using hydrogen-containing silane and an epoxy-containing silane coupling agent to modify the surface of magnesium hydroxide, the flame retardant properties, mechanical properties and bonding properties of silicone rubber can be improved at the same time.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0007] In the first aspect, a hydrosilane having a general structural formula is: ;
[0008] Wherein, A contains 4 to 54 carbon atoms, contains at least one aromatic ring, and does not contain N, S, or P elements. Preferably, A contains at least one ester bond or ether bond;
[0009] In one or more embodiments, the structure of A is selected from:
[0010] , , , , or Any one of .
[0011] In a second aspect, the method for preparing the above-mentioned hydrogen-containing silane comprises: subjecting a diene monomer to a hydrosilylation reaction with a cyclic hydrogen-containing silicone oil to obtain the hydrogen-containing silane.
[0012] Wherein, the diene monomer contains 4 to 54 carbon atoms and contains at least one aromatic ring. Preferably, the diene monomer contains at least one ester bond or ether bond;
[0013] The annular hydrogen-containing silicone oil is tetramethylcyclotetrasiloxane;
[0014] Preferably, the diene monomer is a terminal diene monomer, that is, the unsaturated double bonds are located at both ends of the molecule.
[0015] In one or more embodiments, the diene monomer is selected from: , , , , or Any one of .
[0016] Further, the preparation method of the hydrosilane comprises: performing a hydrosilylation reaction on tetramethylcyclotetrasiloxane and a diene monomer at a molar ratio of 2.5 to 3.5:1; preferably, performing a hydrosilylation reaction on tetramethylcyclotetrasiloxane and a diene monomer at a molar ratio of 2.5 to 3.0:1;
[0017] Furthermore, the preparation method of hydrogen-containing silane includes: adding an inhibitor and a catalyst to the hydrosilylation reaction, reacting the hydrosilylation reaction at 70-90° C. for 2-4 hours, and then heating to 80-100° C. and keeping the temperature for 1-3 hours.
[0018] Wherein, the polymerization inhibitor is selected from p-methylanisole;
[0019] The catalyst is selected from any one of chloroplatinic acid or chloroplatinic acid vinyl complex; preferably, the catalyst is selected from chloroplatinic acid-divinyltetramethyldisiloxane complex.
[0020] Furthermore, the preparation method further comprises: cooling the temperature to 40-60° C. after the reaction is completed and distilling off the solvent under reduced pressure;
[0021] Furthermore, the preparation method further comprises: adding the catalyst remaining in the activated carbon adsorption product, removing the catalyst by suction filtration, and obtaining a hydrogen-containing silane product.
[0022] A third aspect is a use of the above-mentioned hydrosilane as a modifier for surface modification of magnesium hydroxide.
[0023] In a fourth aspect, a surface-modified magnesium hydroxide is obtained by surface-modifying the magnesium hydroxide using the above-mentioned hydrogen-containing silane and silane coupling agent.
[0024] Preferably, in the surface-modified magnesium hydroxide, the silane coupling agent contains at least one epoxy group.
[0025] Preferably, the silane coupling agent is selected from any one or a combination of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane or 3-glycidyloxypropylmethyldiethoxysilane.
[0026] The specific steps of surface modification include:
[0027] S1. Fully mix the above-mentioned hydrogen-containing silane, the silane coupling agent and the alcohol / water mixture, and then add magnesium hydroxide and mix well;
[0028] S2. The uniformly mixed materials in S1 are heated to 80-180° C. to obtain surface-modified magnesium hydroxide.
[0029] Preferably, the silane coupling agent is selected from KH560;
[0030] Preferably, the alcohol is selected from any one or a combination of methanol, ethanol or isopropanol;
[0031] Preferably, the thorough mixing uses mechanical stirring and / or ultrasound;
[0032] Preferably, the average particle size of the magnesium hydroxide is no more than 10 μm.
[0033] Furthermore, the mass ratio of magnesium hydroxide:hydrogen-containing silane to silane coupling agent is (5:1)-(6:1).
[0034] In a fifth aspect, a halogen-free flame-retardant silicone rubber composition comprises the following raw materials: vinyl silicone oil, the surface-modified magnesium hydroxide described above, a cross-linking agent, a tackifier, a structure control agent and a catalyst;
[0035] Wherein, the content of vinyl in the vinyl silicone oil is 0.05-0.5mmol / g;
[0036] The cross-linking agent is selected from hydrogen-containing silicone oil, and the content of active hydrogen in the hydrogen-containing silicone oil is preferably 0.1-1wt%;
[0037] The structure control agent is selected from any one or more of 1-ethynyl-1-cyclohexanol, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-hexynyl-3-ol, and 3-methyl-1-dodecynyl-3-ol;
[0038] The catalyst is selected from any one or more of chloroplatinic acid, chloroplatinic acid-isopropanol complex or chloroplatinic acid-divinyl;
[0039] Preferably, the catalyst is selected from chloroplatinic acid-divinyltetramethyldisiloxane complex;
[0040] Preferably, the effective content of Pt in the catalyst is 2000-5000 ppm.
[0041] The general structural formula of the tackifier is:
[0042] , wherein X and Y are selected from any one of vinyl, allyl, methacryloxypropyl, glycidoxypropyl and isocyanatepropyl, and X and Y are different;
[0043] Preferably, at least one of X and Y is selected from vinyl or allyl, wherein at least one of X and Y contains an unsaturated double bond.
[0044] Furthermore, a halogen-free flame-retardant silicone rubber composition is composed of the following components in parts by mass: 90-110 parts of vinyl silicone oil, 120-180 parts of the surface-modified magnesium hydroxide described above, 1-10 parts of a crosslinking agent, 1-10 parts of a tackifier, 0.1-1 parts of a structure control agent, and 0.01-0.1 parts of a catalyst;
[0045] In a sixth aspect, the method for preparing the above-mentioned halogen-free flame-retardant silicone rubber composition comprises: uniformly mixing the above-mentioned raw materials, adding a catalyst, and then degassing and curing, wherein the curing temperature is 100-200°C.
[0046] A seventh aspect is a use of the halogen-free flame retardant silicone rubber composition as an adhesive.
[0047] The invention has the beneficial effects of introducing an aromatic ring into an annular hydrogen-containing silicone oil through a hydrosilylation reaction to prepare hydrogen-containing silane, using the obtained hydrogen-containing silane and an epoxy-containing silane coupling agent to perform surface modification on magnesium hydroxide in an alcohol aqueous solution, thereby obtaining surface-modified magnesium hydroxide, the hydroxyl groups on the surface of magnesium hydroxide particles are combined with the hydrogen-containing silane and the epoxy-containing silane coupling agent through condensation or hydrogen bonding, and subsequently adding vinyl silicone oil, hydrogen-containing silicone oil, a tackifier, a structure control agent and a catalyst, so as to prepare silicone rubber with more balanced tensile strength and elongation at break, excellent flame retardant effect and stronger bonding performance to the plastic / metal interface. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a morphological diagram of the appearance of silicone rubber ash after oxygen index testing of Examples 7 and 8 and Comparative Examples 1 and 3.
[0049] Figure 2 This is the TG curve of silicone rubber cured product.
[0050] Figure 3This is the DTG curve of silicone rubber cured product. DETAILED DESCRIPTION
[0051] In conjunction with the embodiments of the present invention, the technical solutions in the embodiments are clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. It should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0052] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.
[0053] Example 1
[0054] Preparation of hydrogen-containing silane: 0.365 g of the polymerization inhibitor p-methyl anisole and 0.115 g of the catalyst chloroplatinic acid-divinyltetramethyldisiloxane complex were added to a flask and dissolved with 50 mL of toluene. 199.62 g (0.830 mol) of tetramethylcyclotetrasiloxane and 85.46 g (0.277 mol) of bisphenol A bisallyl ether were dissolved with 75 mL of toluene and added dropwise to the flask at 83 ° C. The reaction process was protected by nitrogen gas in the flask. The material was added dropwise for a total of 3 hours. After the addition, the temperature was raised to 90 ° C and the temperature was kept for 2 hours to terminate the heating. The temperature was then lowered and the solvent was distilled off under reduced pressure at 60 ° C. The catalyst in the activated carbon adsorption product was added in batches, and the catalyst was removed by suction filtration to obtain a hydrogen-containing silane product. The reaction formula is:
[0055]
[0056] Structural confirmation of hydrosilane products: 1H NMR (400 MHz): δ 0.24-0.35 (24H, 0.29(s), 0.30 (s), 0.30 (s), 0.30 (s), 0.30 (s), 0.30 (s)), 0.88-1.05 (4H, 0.95(t, J = 7.50 Hz), 0.98 (t, J = 7.50 Hz)), 1.49 (6H, s), 1.81-1.99 (4H, 1.90 (tt, J = 7.50, 7.43 Hz), 1.90 (tt, J = 7.50, 7.47 Hz)), 3.90-4.05 (4H, 3.97(t, J = 7.47 Hz), 3.98 (t, J = 7.43 Hz)), 6.95-7.07 (4H, 7.01 (ddd, J = 8.87,1.64, 0.55 Hz), 7.01 (ddd, J = 8.87, 1.65, 0.55 Hz)), 7.17-7.30 (4H, 7.24(ddd, J = 8.87, 1.10, 0.55 Hz), 7.24 (ddd, J = 8.87, 1.10, 0.55 Hz)).
[0057] Surface modification of magnesium hydroxide by hydrosilane prepared in Example 1:
[0058] S1. 25 g of the above-mentioned hydrogen-containing silane, 15 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) and 30 mL of ethanol / water mixture (volume ratio 1:1) were mixed and stirred for 10 min and then ultrasonically dispersed for 30 min. Subsequently, 200 g of magnesium hydroxide were added in batches under stirring. The mixture was stirred and reacted for 30 min. After the reaction was completed, a crude product was obtained;
[0059] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0060] Example 2
[0061] Preparation of hydrogen-containing silane: 0.425 g of the polymerization inhibitor p-methyl anisole and 0.125 g of the catalyst chloroplatinic acid-divinyltetramethyldisiloxane complex were added to a flask and dissolved with 50 mL of toluene. 199.62 g (8.30 mol) of tetramethylcyclotetrasiloxane and 117.5 g (0.277 mol) of 2-acrylic acid (1-methylethylidene) di(4,1-phenyleneoxy-2,1-ethylenediyl) ester were dissolved with 85 mL of toluene and added dropwise to the flask at 85 ° C. The reactants in the flask were protected by nitrogen during the reaction process. The materials were added dropwise for a total of 3 hours. After the addition was completed, the temperature was raised to 95 ° C and kept warm for 2 hours to terminate the heating, followed by cooling and distillation at 60 ° C to remove the solvent, and then 18 g of the catalyst in the activated carbon adsorption product was added in batches. The catalyst was removed by suction filtration to obtain a hydrogen-containing silane product, and the reaction formula is:
[0062]
[0063] Structural confirmation of hydrosilane products: 1 H NMR (400 MHz): δ 0.24-0.35 (21H, 0.29(s), 0.30 (s), 0.30 (s), 0.30 (s), 0.30 (s)), 1.22-1.36 (4H, 1.29 (t, J =7.09 Hz), 1.30 (t, J = 7.08 Hz)), 1.49 (6H, s), 2.64-2.82 (4H, 2.70 (t, J =7.09 Hz), 2.75 (t, J = 7.08 Hz)), 4.24 (2H, t, J = 7.39 Hz), 4.42 (2H, t, J =7.39 Hz), 5.68 (2H, s), 6.92-7.16 (4H, 6.98 (ddd, J = 8.13, 1.25, 0.55 Hz),7.09 (ddd, J = 8.50, 1.29, 0.55 Hz)), 7.18-7.31 (4H, 7.24 (ddd, J = 8.50,1.10, 0.55 Hz), 7.25 (ddd, J = 8.13, 1.06, 0.55 Hz)).
[0064] Surface modification of magnesium hydroxide by hydrosilane prepared in Example 2:
[0065] S1. 25 g of the above-mentioned hydrogen-containing silane, 15 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) and 30 mL of ethanol / water mixture (volume ratio 1:1) were mixed and stirred for 10 min and then ultrasonically dispersed for 30 min. Subsequently, 200 g of magnesium hydroxide were added in batches under stirring. The mixture was stirred and reacted for 30 min. After the reaction was completed, a crude product was obtained;
[0066] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0067] Example 3
[0068] Preparation of hydrosilane: 0.398 g of p-methylanisole, an inhibitor, and 0.115 g of a catalyst chloroplatinic acid-divinyltetramethyldisiloxane complex were added to a flask and dissolved with 50 mL of toluene. 199.62 g (0.830 mol) of tetramethylcyclotetrasiloxane and 74.25 g (0.302 mol) of diallyl phthalate were dissolved with 70 mL of toluene and added dropwise to a flask at 82 ° C. The reaction was protected by nitrogen in the flask. The material was added dropwise for a total of 3 hours. After the addition, the temperature was raised to 92 ° C and the temperature was kept for 2 hours to terminate the heating. The solvent was then removed by vacuum distillation at 60 ° C. The catalyst in the activated carbon adsorption product was added in batches of 16 g. The catalyst was removed by suction filtration to obtain a hydrosilane product. The reaction formula is:
[0069]
[0070] Structural confirmation of hydrosilane products: 1 H NMR (400 MHz): δ 0.25-0.35 (18H, 0.30(s), 0.30 (s)), 0.98 (4H, t, J = 7.50 Hz), 1.91 (4H, tt, J = 7.52, 7.50 Hz), 4.18 (4H, t, J = 7.52 Hz), 7.64-7.82 (4H, 7.71 (ddd, J = 7.81, 7.70, 1.32Hz), 7.76 (ddd, J = 7.81, 1.32, 0.54 Hz)).
[0071] Surface modification of magnesium hydroxide by hydrosilane prepared in Example 3:
[0072] S1, 25g of the above-mentioned hydrogen-containing silane, 15g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) and 30mL of ethanol / water mixture (volume ratio 1:1) were mixed and stirred for 10min and then ultrasonically dispersed for 30min, and then 210g of magnesium hydroxide was added in batches under stirring, and the mixture was continuously stirred for reaction for 30min, and a crude product was obtained after the reaction was completed;
[0073] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0074] Example 4
[0075] Preparation of hydrogen-containing silane: 0.412 g of the polymerization inhibitor p-methyl anisole and 0.125 g of the catalyst chloroplatinic acid-divinyltetramethyldisiloxane complex were added to a flask and dissolved with 50 mL of toluene. 199.62 g (0.830 mol) of tetramethylcyclotetrasiloxane and 119.26 g (0.277 mol) of 9,9-bis(4-allyloxyphenyl)fluorene were dissolved with 85 mL of toluene and added dropwise to the flask at 87 ° C. The reactants in the flask were protected by nitrogen during the reaction process. The materials were added dropwise for a total of 3 hours. After the addition was completed, the temperature was raised to 95 ° C and kept warm for 2 hours to terminate the heating, followed by cooling and removing the solvent by reduced pressure distillation at 60 ° C. Then 18 g of the catalyst in the activated carbon adsorption product was added in batches, and the catalyst was removed by suction filtration to obtain a hydrogen-containing silane product, and the reaction formula is:
[0076]
[0077] Structural confirmation of hydrosilane products: 1H NMR (400 MHz): δ 0.24-0.36 (24H, 0.29(s), 0.30 (s), 0.31 (s)), 0.95 (4H, t, J = 7.50 Hz), 1.90 (4H, tt, J = 7.50,7.43 Hz), 3.98 (4H, t, J = 7.43 Hz), 6.85 (4H, ddd, J = 8.50, 1.09, 0.55 Hz), 7.14 (4H, ddd, J = 8.50, 1.13, 0.55 Hz), 7.31-7.45 (4H, 7.38 (ddd, J = 8.47,6.90, 1.42 Hz), 7.38 (ddd, J = 8.07, 6.90, 1.50 Hz)), 7.64 (2H, ddd, J =8.07, 1.42, 0.52 Hz), 7.85 (2H, ddd, J = 8.47, 1.50, 0.52 Hz).
[0078] Surface modification of magnesium hydroxide by hydrosilane prepared in Example 4:
[0079] S1. Mix 25g of the above-mentioned hydrogen-containing silane, 15g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) and 30mL of ethanol / water mixture (volume ratio 1:1) and stir for 10min to fully mix, then ultrasonically disperse for 30min, then add 220g of magnesium hydroxide in batches while stirring, and continue stirring the mixture for 30min to obtain a crude product after the reaction is completed;
[0080] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0081] Example 5
[0082] Preparation of hydrogen-containing silane: 0.428 g of the polymerization inhibitor p-methyl anisole and 0.125 g of the catalyst chloroplatinic acid-divinyltetramethyldisiloxane complex were added to a flask and dissolved with 50 mL of toluene. 199.62 g (0.830 mol) of tetramethylcyclotetrasiloxane and 62.30 g (0.302 mol) of 4,4'-divinyl-1,1'-biphenyl were dissolved with 70 mL of toluene and added dropwise to the flask at 83 ° C. The reactants in the flask were protected by nitrogen during the reaction process. The materials were added dropwise for a total of 3 hours. After the addition was completed, the temperature was raised to 92 ° C and kept warm for 2 hours to terminate the heating, followed by cooling and distillation at 60 ° C to remove the solvent, and then 16 g of the catalyst in the activated carbon adsorption product was added in batches. The catalyst was removed by suction filtration to obtain a hydrogen-containing silane product, and the reaction formula is:
[0083]
[0084] Structural confirmation of hydrosilane products: 1 H NMR (400 MHz): δ 0.25-0.35 (18H, 0.30(s), 0.30 (s)), 0.98 (4H, t, J = 7.50 Hz), 1.91 (4H, tt, J = 7.52, 7.50 Hz), 4.18 (4H, t, J = 7.52 Hz), 7.64-7.82 (4H, 7.71 (ddd, J = 7.81, 7.70, 1.32Hz), 7.76 (ddd, J = 7.81, 1.32, 0.54 Hz)).
[0085] Surface modification of magnesium hydroxide by hydrosilane prepared in Example 5:
[0086] S1. 25 g of the above-mentioned hydrogen-containing silane, 15 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) and 30 mL of ethanol / water mixture (volume ratio 1:1) were mixed and stirred for 10 min and then ultrasonically dispersed for 30 min. Subsequently, 200 g of magnesium hydroxide were added in batches under stirring. The mixture was stirred and reacted for 30 min. After the reaction was completed, a crude product was obtained;
[0087] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0088] Example 6
[0089] Preparation of hydrogen-containing silane: 0.428 g of the polymerization inhibitor p-methyl anisole and 0.125 g of the catalyst chloroplatinic acid-divinyltetramethyldisiloxane complex were added to a flask and dissolved with 50 mL of toluene. 199.62 g (0.830 mol) of tetramethylcyclotetrasiloxane and 67.13 g (0.302 mol) of 4,4'-divinyl-1,1'-biphenyl ether were dissolved with 70 mL of toluene and added dropwise to the flask at 83 ° C. The reactants in the flask were protected by nitrogen during the reaction process. The materials were added dropwise for a total of 3 hours. After the addition was completed, the temperature was raised to 92 ° C and kept warm for 2 hours to terminate the heating, followed by cooling and removing the solvent by reduced pressure distillation at 60 ° C. Then 16 g of the catalyst in the activated carbon adsorption product was added in batches, and the catalyst was removed by suction filtration to obtain a hydrogen-containing silane product, and the reaction formula is:
[0090]
[0091] Structural confirmation of hydrosilane products: 1 H NMR (400 MHz): δ 0.24-0.36 (24H, 0.29(s), 0.30 (s), 0.31 (s)), 1.14 (4H, t, J = 7.49 Hz), 2.74 (4H, t, J = 7.49Hz), 6.91 (4H, ddd, J = 8.30, 1.79, 0.55 Hz), 7.05 (4H, ddd, J = 8.30, 1.00, 0.55 Hz).
[0092] Surface modification of magnesium hydroxide by hydrogen-containing silane prepared in Example 6:
[0093] S1. 25 g of the above-mentioned hydrogen-containing silane, 15 g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) and 30 mL of ethanol / water mixture (volume ratio 1:1) were mixed and stirred for 10 min and then ultrasonically dispersed for 30 min. Subsequently, 200 g of magnesium hydroxide were added in batches under stirring. The mixture was stirred and reacted for 30 min. After the reaction was completed, a crude product was obtained;
[0094] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0095] Components in the addition silicone rubber formula:
[0096] Vinyl silicone oil with a vinyl content of 1.92% (Zhejiang Xin'an Chemical Group) and vinyl silicone oil with a vinyl content of 0.8% (Zhejiang Xin'an Chemical Group) were pre-mixed in a mass ratio of 4:6. After mixing, the terminal vinyl content of the mixed vinyl silicone oil was calculated to be 0.168 mmol / g, and the viscosity of the mixed vinyl silicone oil was 2270 mPa·s.
[0097] The cross-linking agent was hydrogen-containing silicone oil (Shandong Dayi Chemical Co., Ltd.) with an active hydrogen content of 0.50 wt %;
[0098] The structure control agent is 1-ethynyl-1-cyclohexanol (Shanghai MacLean Biochemical Technology Co., Ltd.), with an effective content of 99%;
[0099] The catalyst is chloroplatinic acid-divinyltetramethyldisiloxane complex, and the effective content of Pt is 3000ppm (Dongguan Beiteli New Materials);
[0100] The tackifier was prepared according to the following method: 87.12 g (0.5 mol) of trimethylolpropane monoallyl ether and 110.17 g (0.5 mol) of 3-[(2,3)-epoxypropoxy]propylmethyldimethoxysilane were added to a flask, stirred evenly at room temperature, and then 2 g of catalyst tetrabutyl titanate (TNBT) was added. The flask was continuously stirred and nitrogen gas was introduced. Under this condition, the temperature was raised to 95°C for reaction for 3 hours, and the temperature was lowered to 65°C and the reaction was changed to reduced pressure for 1 hour. The preparation reaction formula of the tackifier is as follows:
[0101]
[0102] Example 7
[0103] 100 parts of the mixed vinyl silicone oil and 150 parts of surface-modified magnesium hydroxide prepared in Example 1 were stirred evenly in a high-speed disperser to obtain a base material, and then 5 parts of hydrogenated silicone oil, 4.5 parts of a tackifier and 0.5 parts of 1-ethynyl-1-cyclohexanol were added and mixed evenly, and finally 0.05 parts of chloroplatinic acid-divinyltetramethyldisiloxane complex with an effective content of Pt of 3000ppm was added, and finally the mixture was placed in a vacuum drying oven for vacuum degassing for 15 minutes to obtain a halogen-free flame retardant addition silicone rubber.
[0104] Example 8
[0105] The silicone rubber formula uses 7 parts of hydrogenated silicone oil and 2.5 parts of tackifier, and the rest is the same as Example 7.
[0106] Example 9
[0107] The silicone rubber formula uses 150 parts of surface-modified magnesium hydroxide prepared in Example 2, and the rest is the same as in Example 7.
[0108] Example 10
[0109] The silicone rubber formula uses 7 parts of hydrogenated silicone oil and 2.5 parts of tackifier, and the rest is the same as Example 7.
[0110] Embodiment 11
[0111] The silicone rubber formula uses 150 parts of surface-modified magnesium hydroxide prepared in Example 3, and the rest is the same as in Example 7.
[0112] Example 12
[0113] The silicone rubber formula uses 7 parts of hydrogenated silicone oil and 2.5 parts of tackifier, and the rest is the same as Example 7.
[0114] Example 13
[0115] The silicone rubber formula uses 150 parts of surface-modified magnesium hydroxide prepared in Example 4, and the rest is the same as in Example 7.
[0116] Embodiment 14
[0117] The silicone rubber formula uses 7 parts of hydrogenated silicone oil and 2.5 parts of tackifier, and the rest is the same as Example 7.
[0118] Embodiment 15
[0119] The silicone rubber formula uses 150 parts of surface-modified magnesium hydroxide prepared in Example 5, and the rest is the same as in Example 7.
[0120] Example 16
[0121] The silicone rubber formula uses 7 parts of hydrogenated silicone oil and 2.5 parts of tackifier, and the rest is the same as Example 7.
[0122] Embodiment 17
[0123] The silicone rubber formula uses 150 parts of surface-modified magnesium hydroxide prepared in Example 6, and the rest is the same as in Example 7.
[0124] Embodiment 18
[0125] The silicone rubber formula uses 7 parts of hydrogenated silicone oil and 2.5 parts of tackifier, and the rest is the same as Example 7.
[0126] Comparative Example 1
[0127] 100 parts of the mixed vinyl silicone oil and 150 parts of magnesium hydroxide are stirred evenly in a high-speed disperser to obtain a base material, and then 5 parts of hydrogenated silicone oil, 4.5 parts of a tackifier and 0.5 parts of 1-ethynyl-1-cyclohexanol are added and mixed evenly, and finally 0.05 parts of chloroplatinic acid-divinyltetramethyldisiloxane complex with an effective content of Pt of 3000ppm is added, and finally the mixture is placed in a vacuum drying oven for vacuum degassing for 15 minutes to obtain a halogen-free flame retardant addition silicone rubber.
[0128] Comparative Example 2
[0129] Surface modification of magnesium hydroxide using the hydrosilane prepared in Example 1:
[0130] S1, 25g of the above-mentioned hydrosilane was mixed with 30mL of ethanol and stirred for 10min to fully mix, and then ultrasonically dispersed for 30min, and then 200g of magnesium hydroxide was added in batches under stirring, and the mixture was continuously stirred for reaction for 30min, and a crude product was obtained after the reaction was completed;
[0131] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0132] 100 parts of the mixed vinyl silicone oil and 150 parts of the surface-modified magnesium hydroxide prepared by the above method are stirred evenly in a high-speed disperser to obtain a base material, and then 5 parts of hydrogenated silicone oil, 4.5 parts of a tackifier and 0.5 parts of 1-ethynyl-1-cyclohexanol are added and mixed evenly, and finally 0.05 parts of chloroplatinic acid-divinyltetramethyldisiloxane complex with an effective content of Pt of 3000ppm is added, and finally the mixture is placed in a vacuum drying oven for vacuum degassing for 15 minutes to obtain a halogen-free flame retardant addition silicone rubber.
[0133] Comparative Example 3
[0134] Surface modification of magnesium hydroxide using KH560 alone:
[0135] S1, 15g of silane coupling agent 3-glycidyloxypropyltrimethoxysilane (KH560) was mixed with 30mL of ethanol and stirred for 10min to fully mix, and then ultrasonically dispersed for 30min, and then 200g of magnesium hydroxide was added in batches under stirring, and the mixture was continuously stirred for reaction for 30min, and a crude product was obtained after the reaction was completed;
[0136] S2. The crude product obtained in step S1 is baked at 105° C. for 2 h to obtain surface-modified magnesium hydroxide.
[0137] 100 parts of the mixed vinyl silicone oil and 150 parts of the surface-modified magnesium hydroxide prepared by the above method are stirred evenly in a high-speed disperser to obtain a base material, and then 5 parts of hydrogenated silicone oil, 4.5 parts of a tackifier and 0.5 parts of 1-ethynyl-1-cyclohexanol are added and mixed evenly, and finally 0.05 parts of chloroplatinic acid-divinyltetramethyldisiloxane complex with an effective content of Pt of 3000ppm is added, and finally the mixture is placed in a vacuum drying oven for vacuum degassing for 15 minutes to obtain a halogen-free flame retardant addition silicone rubber.
[0138] Curing conditions: The silicone rubber materials prepared in Examples 7-18 and Comparative Examples 1-3 were placed in a flat vulcanizer and heated and cured at 150° C. for 2 min. Finally, the materials were cooled to room temperature for use.
[0139] Test Section
[0140] The tensile strength and elongation at break were measured using an electronic universal testing machine in accordance with GB / T 528-2009. The specimen was dumbbell-shaped, 2 mm thick, and the tensile rate was 500 mm / min. The cured specimen was cooled and placed at room temperature for 12 hours before testing the mechanical properties.
[0141] Flame retardant performance test: refer to GB / T 2406.2-2009 method B, use oxygen index meter to test the limiting oxygen index of the sample; refer to ISO 5660, use FTT cone calorimeter to test the flame retardant performance of 100×100×3mm 3 The sheet is tested to obtain the ignition time (TTI). The shorter the ignition time, the worse the flame retardant performance of the material to be tested.
[0142] The appearance of the silicone rubber ash after the oxygen index test was completed. The silicone rubber samples prepared in Comparative Examples 1 and 3 and Examples 7 and 8 were tested for limiting oxygen index. After the test, the ash was photographed to observe the external appearance. Figure 1 shown.
[0143] Thermogravimetric analysis: The silicone rubber without flame retardant added, the silicone rubber prepared in Comparative Examples 1-3, and the silicone rubber prepared in Examples 7 and 8 were subjected to thermogravimetric testing in a nitrogen atmosphere. The temperature was raised from room temperature to 700°C at a rate of 20°C / min. The weight loss percentage and the weight loss rate were plotted against the temperature to obtain the TG curve and the DTG curve, respectively. Figure 2 and Figure 3 shown.
[0144] Adhesion test of metal and plastic interface: The adhesives of Examples 7-18 and Comparative Examples 1-4 were used to perform tensile shear tests on the interface of PET sheet and aluminum sheet after bonding. The curing conditions were 130°C*2min. Ten specimens were made for each sample. The tensile shear test was used to observe whether the addition silicone rubber after curing showed cohesive failure, or whether the silicone rubber / aluminum and silicone rubber / PET bonding interfaces showed interfacial failure.
[0145] The test results of Examples 7-18 and Comparative Examples 1-3 are listed in Table 1.
[0146] Table 1
[0147]
[0148] According to the data analysis of Table 1, the addition silicone rubber with magnesium hydroxide modified by adding hydrogen-containing silane and KH560 has more balanced tensile strength and elongation at break, and the limiting oxygen index is ≥34%, and the ignition time is ≥67s. Compared with the comparative examples 1 and 3 with the same amount of magnesium hydroxide, the flame retardant performance has obvious advantages, and compared with the comparative example 2 with the same amount of magnesium hydroxide, the mechanical properties have obvious advantages. At the same time, the adhesion of silicone rubber to plastic and metal can achieve complete cohesive failure after tensile shearing, and there is no interface damage between silicone rubber and adherend, indicating that the surface-modified magnesium hydroxide can also play the role of a tackifier, and the introduction of polar ester bonds or ether bonds in hydrogen-containing silane can provide adhesion at the metal / plastic interface. Example 5 does not introduce polar ester bonds or ether bonds in the preparation process of hydrogen-containing silane, and the bonding effect of the addition silicone rubber of corresponding Examples 15 and 16 is relatively low.
[0149] Comparative Example 1 does not use hydrogen-containing silane and KH560 to modify the surface of magnesium hydroxide. The hydrogen surface of magnesium hydroxide can adsorb water molecules and dissociate with water molecules to a certain extent to form surface hydroxyl groups. The surface hydroxyl groups give magnesium hydroxide a certain hydrophilicity, resulting in poor compatibility with strongly hydrophobic monomers such as vinyl silicone oil and tackifiers. After curing, it cannot be evenly dispersed in the silicone rubber molecular chain, resulting in very low mechanical properties. The flame retardant effect is not ideal compared with Examples 7-18. From the perspective of interfacial bonding effect, Comparative Example 1 has poor bonding strength at the metal / plastic interface.
[0150] In Comparative Example 2, only the hydrogen-containing silane prepared in Example 1 was used to modify the surface of magnesium hydroxide, and KH560 which can condense with silanol groups after hydrolysis was not used. As a result, the reactive silicon-hydrogen bonds and silanol contents on the surface of the magnesium hydroxide after modification were too high, which could provide more cross-linking sites, thereby increasing the overall cross-linking degree of the silicone rubber and significantly reducing its elongation at break. In addition, the cross-linking sites were too dense, which made it difficult for the tackifier in the silicone rubber to form an effective interaction with the surface of the adherend, thereby reducing the bonding performance.
[0151] In Comparative Example 3, only KH560 was used to modify the surface of magnesium hydroxide, which lacked the cross-linking sites of hydrogen-containing silane and the carbon skeleton structure containing aromatic rings, so that the tensile strength of the silicone rubber was insufficient and the flame retardant effect was poor. At the same time, due to the lack of hydrogen-containing silane, the adhesion to the metal / plastic adherend interface was not high.
[0152] Through Figure 1 From the observation of the ashes of the silicone rubber after the oxygen index test, it can be seen that the ashes of Comparative Examples 1 and 3 are brittle white powders, which are SiO2 generated after the silicone rubber is burned. In Examples 7 and 8, the powder of the surface of magnesium hydroxide is modified by adding the hydrogen-containing silane prepared in Example 1 and KH560. The internal cross-section of the dense coating layer of the ashes after combustion is a gray carbon layer, indicating that the carbon skeleton structure containing aromatic rings introduced in the hydrogen-containing silane can be coated on the surface of magnesium hydroxide to play a carbonizing role, thereby achieving heat insulation and flame retardant effects. This carbon layer prevents heat and oxygen from being transferred to the internal material of the silicone rubber to delay the spread of flames, thereby improving the limiting oxygen index of the silicone rubber.
[0153] Through Figure 2 The TG curve of Figure 3 From the DTG curve analysis, it can be seen that the addition-type silicone rubber itself has a high thermal stability. Its TG curve has only one main thermal degradation stage, and degradation begins to occur when the temperature rises to about 480°C, indicating that the thermal stability of silicone rubber is relatively high under inert atmosphere and fast heating rate. The TG and DTG curve trends of the silicone rubber system with magnesium hydroxide or surface-modified magnesium hydroxide are basically similar, and two degradation stages appear. The decomposition reaction begins at about 320°C, entering the first degradation stage. After the temperature rises to about 380°C, the sample enters the second degradation stage. The weight loss percentage of Comparative Example 3, which only introduces KH560 on the surface, is lower than that of Comparative Example 1, which is not surface-modified, because the carbon layer of the aromatic ring carbon skeleton in the lack of hydrogen-containing silane loses weight. Comparative Example 2, Examples 7 and 8 have a higher weight loss percentage, which is due to the modification of the surface of magnesium hydroxide by hydrogen-containing silane containing aromatic ring carbon skeletons. During the combustion process, the thermal decomposition of these carbon layers can absorb more heat and produce CO2 to dilute the concentration of oxygen or other combustible gases to enhance the flame retardant effect of silicone rubber.
[0154] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.
Claims
1. A hydrosilane, characterized in that: The general structural formula of hydrosilane is: ; A contains 4 to 54 carbon atoms, contains at least one aromatic ring, and does not contain N, S, or P elements.
2. A method for preparing hydrogen-containing silane according to claim 1, characterized in that: The product is obtained by the hydrosilylation reaction of diene monomer and cyclic hydrogen-containing silicone oil.
3. The preparation method according to claim 2, characterized in that: The annular hydrogen-containing silicone oil is reacted with a diene monomer in a molar ratio of (2.5-3.5):1, wherein the diene monomer contains 4 to 54 carbon atoms and contains at least one aromatic ring; And / or, the annular hydrogen-containing silicone oil is tetramethylcyclotetrasiloxane; and / or, the diene monomer is a terminal diene monomer; and / or, performing a hydrosilylation reaction on the annular hydrogen-containing silicone oil and the diene monomer in a molar ratio of (2.5-3.0):1; And / or, the preparation method of hydrogen-containing silane comprises: adding a polymerization inhibitor and a catalyst to the reaction, reacting at 70-90° C. for 2-4 hours, then heating to 80-100° C. and keeping warm for 1-3 hours, wherein the polymerization inhibitor is selected from p-methyl anisole, and the catalyst is selected from any one of chloroplatinic acid or chloroplatinic acid vinyl complex; And / or, the preparation method of hydrosilane comprises: cooling to 40-60° C. after the reaction is completed and distilling off the solvent under reduced pressure; And / or, the method for preparing hydrogen-containing silane comprises: adding a catalyst remaining in the activated carbon adsorption product, removing the catalyst by suction filtration, and obtaining a hydrogen-containing silane product.
4. A use, characterized in that: Use of the hydrosilane described in claim 1 as a modifier for surface modification of magnesium hydroxide.
5. A surface-modified magnesium hydroxide, characterized in that: The magnesium hydroxide is obtained by surface-modifying the magnesium hydroxide using the hydrogen-containing silane and the silane coupling agent as claimed in claim 1.
6. The surface-modified magnesium hydroxide according to claim 5, characterized in that The silane coupling agent contains at least one epoxy group; And / or, the specific steps of the surface modification include: S1, fully mixing the hydrosilane, the silane coupling agent and the alcohol / water mixture, and then adding magnesium hydroxide and mixing evenly; S2, heating the uniformly mixed materials in S1 to 80-180° C. to obtain surface-modified magnesium hydroxide; And / or, the mass ratio of magnesium hydroxide:hydrogen-containing silane to the total amount of silane coupling agent is (5:1)-(6:1).
7. A halogen-free flame-retardant silicone rubber cured product, characterized in that: The invention comprises the following raw materials: vinyl silicone oil, the surface-modified magnesium hydroxide according to any one of claims 5 to 6, a cross-linking agent, a tackifier, a structure control agent and a catalyst.
8. The halogen-free flame-retardant silicone rubber cured product according to claim 7, characterized in that: The vinyl content in the vinyl silicone oil is 0.05-0.5 mmol / g; And / or, the cross-linking agent is hydrogen-containing silicone oil, and the content of active hydrogen in the hydrogen-containing silicone oil is 0.1-1wt%; and / or, the structure control agent is selected from any one or more of 1-ethynyl-1-cyclohexanol, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butynyl-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-hexynyl-3-ol and 3-methyl-1-dodecynyl-3-ol; And / or, the catalyst is selected from any one or more of chloroplatinic acid, chloroplatinic acid-isopropanol complex or chloroplatinic acid-divinyl; And / or, the general structural formula of the tackifier is: , wherein X and Y are selected from any one of vinyl, allyl, methacryloxypropyl, glycidoxypropyl and isocyanatepropyl, and X and Y are different; And / or, the halogen-free flame-retardant silicone rubber cured product composition is composed of the following components in parts by weight: 90-110 parts of vinyl silicone oil, 120-180 parts of the surface-modified magnesium hydroxide, 1-10 parts of a cross-linking agent, 1-10 parts of a tackifier, and 0.1-1 parts of a structure control agent.
9. A method for preparing a halogen-free flame-retardant silicone rubber composition, characterized in that: The raw materials described in claim 7 are mixed uniformly, and after adding a catalyst, degassing and curing are performed at a curing temperature of 100-200°C.
10. A use, characterized in that: Use of the halogen-free flame-retardant silicone rubber composition according to any one of claims 7 to 8 as an adhesive.
Citation Information
Patent Citations
Modified magnesium hydroxide, preparation method thereof and application thereof in polymer
CN101787223A
Curable composition for optical material
CN102471580A
Modified hydrogen-containing cyclotetrasiloxane bonding accelerant as well as preparation method and application thereof
CN103360422A
Silicone pressure-sensitive adhesive composition having improved substrate adhesion and pressure-sensitive adhesive article
CN104877622A
Flame resistant type room temperature vulcanizing liquid silicone rubber
CN106167621A
Cited By
Coal mine underground flame-retardant aramid rope conveying belt and preparation method thereof
CN121912672A
High and low temperature resistant composite cable material for automobile charging pile and preparation method of high and low temperature resistant composite cable material
CN122405003A